GIJZELING DALAM TEORI DAN PRAKTEK ACARA PERDATA DI INDONESIA - Gandes Candra Kirana (Faculty of Law, Trisakti University, 2021)
The definition of gijzeling according to Article 1 of PERMA No. 1 of 2000 that gijzeling is defined by the term